Alternations in the gut microbiota and metabolome with newly diagnosed unstable angina. (March 2022) - Liu, Xuezhen; Shen, Miaoyan; Yan, Han; Long, Pinpin; Jiang, Haijing; Zhang, Yizhi; Zhou, Lue; Yu, Kuai; Qiu, Gaokun; Yang, Handong; Li, Xiulou; Min, Xinwen; et al.
Abstract: Gut microbiota plays an important role in coronary heart disease, but its compositional and functional changes in unstable angina (UA) remain unexplored. We performed metagenomic sequencing of 133 newly diagnosed UA patients and 133 sex- and age-matched controls, and profiled the fecal and plasma metabolomes in 30 case-control pairs. The alpha diversity of gut microbiota was increased in UA patients: the adjusted odds ratios (ORs) per standard deviation increase in Shannon and Simpson indices were 1.30 (95% confidence interval, 1.01–1.70) and 1.36 (1.05–1.81), respectively. Two common species (depleted Klebsiella pneumoniae and enriched Streptococcus parasanguinis ; P ≤ 0.002) and three rare species (depleted Weissella confusa, enriched Granulicatella adiacens and Erysipelotrichaceae bacterium 6_1_45; P ≤ 0.005) were associated with UA. The UA-associated gut microbiota was depleted in the pathway of L -phenylalanine degradation ( P = 0.001), primarily contributed by Klebsiella pneumoniae . Consistently, we found increased circulating phenylalanine in UA patients (OR = 2.76 [1.17–8.16]). Moreover, S treptococcus parasanguinis was negatively correlated with fecal citrulline (Spearman's r s = −0.470, P = 0.009), a metabolite depleted in UA patients (OR = 0.26 [0.08–0.63]). These findings are informative to help understand the metabolic connection between gut microbiota and UA.